2017
DOI: 10.1289/ehp332
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers in Human Milk and Serum from the U.S. EPA MAMA Study: Modeled Predictions of Infant Exposure and Considerations for Risk Assessment

Abstract: Background:Serum concentrations of polybrominated diphenyl ethers (PBDEs) in U.S. women are believed to be among the world’s highest; however, little information exists on the partitioning of PBDEs between serum and breast milk and how this may affect infant exposure.Objectives:Paired milk and serum samples were measured for PBDE concentrations in 34 women who participated in the U.S. EPA MAMA Study. Computational models for predicting milk PBDE concentrations from serum were evaluated.Methods:Samples were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Despite the fact that commercial formulations are no longer produced in, or imported into, the United States, PBDEs are ubiquitous in human serum and breast milk samples. Recent data from the Methods Advancement for Milk Analysis (MAMA) Study showed that the median serum concentration of BDE-47 was 18.6 ng/g lipid and 3.9 ng/g lipid for BDE-99 (Marchitti et al, 2017). Median breast milk concentrations for BDE-47 were observed in the same study to be 31.5 ng/g lipid, and 6 ng/g lipid for BDE-99.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite the fact that commercial formulations are no longer produced in, or imported into, the United States, PBDEs are ubiquitous in human serum and breast milk samples. Recent data from the Methods Advancement for Milk Analysis (MAMA) Study showed that the median serum concentration of BDE-47 was 18.6 ng/g lipid and 3.9 ng/g lipid for BDE-99 (Marchitti et al, 2017). Median breast milk concentrations for BDE-47 were observed in the same study to be 31.5 ng/g lipid, and 6 ng/g lipid for BDE-99.…”
Section: Introductionmentioning
confidence: 84%
“…80%-90% of total PBDEs in these mixtures (Sanders et al, 2005;LaA Guardia et al, 2006). are also two of the most prevalent PBDE congeners found in human samples (Sjödin et al, 2001;Schecter et al, 2003;Imm et al, 2009;Marchitti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PBDEs are widely present in the household and environment and have attracted people's attention because of their toxic action on animals including neurotoxicity, reproductive toxicity, hepatotoxicity, and endocrine toxicity. PBDEs have been detected in the blood, lipid tissue, and breast milk of human [ 30 32 ], which makes up a potential health risk. The investigations show that PBDEs significantly affect infant birth weight and birth length, thyroid function in young children, and neurodevelopment [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of current research is dedicated to identifying chemical contaminants in traditional matrices like blood or urine, with much less focus on human milk, although it is known that chemicals in a mother’s body can be transferred to her milk from recent chemical exposures or from chemicals that were stored in her fat and then remobilized during pregnancy and lactation (LaKind, Berlin, & Naiman, 2001; Landrigan, Sonawane, Mattison, McCally, & Garg, 2002). Prior human milk studies have focused on persistent organic pollutants (POPs) such as DDT, PCBs (Schlumpf et al, 2010; Weldon et al, 2011), and PBDEs that are sequestered in adipose stores in the body (Guo et al, 2016; Hoffman et al, 2016; Kalantzi et al, 2004; Marchitti, Fenton, Mendola, Kenneke, & Hines, 2017; Schecter et al, 2003; Schlumpf et al, 2010). Other classes of contaminants have been detected but are less frequently studied, including current-use pesticides (Schlumpf et al, 2010; Weldon et al, 2011), BPA (Mendonca, Hauser, Calafat, Arbuckle, & Duty, 2014), and chemicals related to personal care product exposure such as parabens (Schlumpf et al, 2010), phthalates (Fromme, Gruber et al, 2011; Hines, Calafat, Silva, Mendola, & Fenton, 2009; Kim et al, 2015; Main et al, 2006; Schlumpf et al, 2010; Zhu, Phillips, Feng, & Yang, 2006; Zimmermann, Gruber, Schlummer, Smolic, & Fromme, 2012), and triclosan (Dayan, 2007).…”
Section: Introductionmentioning
confidence: 99%